REVIEWING THE LEGAL CERTAINTY OF THE NATIONAL EXAMINATION - Dadang Gandhi (Universitas Muhammadiyah Tangerang, 2021)
Whereas Article 31 Paragraph (2) of the 1945 Constitution (before the amendment) is the legal basis for the formation of Law Number 2 of 1989 concerning the National Education System (Law on National Education System), furthermore based on the provisions of Article 31 Paragraph (2) of the Law. The 1945 Constitution of the Republic of Indonesia (UUDNRI 1945) resulted from the amendment that has formed Law Number 20 of 2003 concerning the National Education System (New National Education System) as a substitute for the National Education System Law. According to Article 58 paragraph (1) and paragraph (2) of the new National Education System, provisions related to